Sliding Cells. The Situated Making of Bio-Objects in IVF - Manuela Perrotta; Kristin Spilker; Stefano Crabu (Tecnoscienza, 2018)
The introduction aims to introduce the topic under investigation in this thematic section and underline connections among the three essays. Taken as a whole, the thematic section explores “ontological shiftings” in life sciences, i.e. how reproductive cells can assume different meanings, roles and values according to the situated processes in which they are embedded. The section sheds light on the co-production of reproductive cells and “moral landscapes”, showing how conventions concerning biological “properties” and “qualities” are intertwined with social norms and values about family, kinship, and gender relations. The term “sliding cells” is meant to evoke the unstable boundaries between “Nature” and “Culture” explored in this section.